Strigolactone Alleviates the Adverse Effects of Salt Stress on Seed Germination in Cucumber by Enhancing Antioxidant Capacity - Changxia Li; Xuefang Lu; Yunzhi Liu; Junrong Xu; Wenjin Yu (MDPI AG, 2023)
Strigolactones (SLs), as a new phytohormone, regulate various physiological and biochemical processes, and a number of stress responses, in plants. In this study, cucumber 'Xinchun NO. 4' is used to study the roles of SLs in seed germination under salt stress. The results show that the seed germination significantly decreases with the increase in the NaCl concentrations (0, 1, 10, 50, and 100 mM), and 50 mM NaCl as a moderate stress is used for further analysis. The different concentrations of SLs synthetic analogs GR24 (1, 5, 10, and 20 μM) significantly promote cucumber seed germination under NaCl stress, with a maximal biological response at 10 μM. An inhibitor of strigolactone (SL) synthesis TIS108 suppresses the positive roles of GR24 in cucumber seed germination under salt stress, suggesting that SL can alleviate the inhibition of seed germination caused by salt stress. To explore the regulatory mechanism of SL-alleviated salt stress, some contents, activities, and genes related to the antioxidant system are measured. The malondialdehyde (MDA), H2O2, O2−, and proline contents are increased, and the levels of ascorbic acid (AsA) and glutathione (GSH) are decreased under salt stress conditions, while GR24 treatment reduces MDA, H2O2, O2−, and proline contents, and increases AsA and GSH contents during seed germination under salt stress. Meanwhile, GR24 treatment enhances the decrease in the activities of antioxidant enzymes caused by salt stress [superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX)], following which antioxidant-related genes SOD, POD, CAT, APX, and GRX2 are up-regulated by GR24 under salt stress. However, TIS108 reversed the positive effects of GR24 on cucumber seed germination under salt stress. Together, the results of this study revealed that GR24 regulates the expression levels of genes related to antioxidants and, therefore, regulates enzymatic activity and non-enzymatic substances and enhances antioxidant capacity, alleviating salt toxicity during seed germination in cucumber.